Satire in the Holy Quran - sohrab morovati; Amin zolfaghari far (تحقیقات علوم قرآن و حدیث, 2013)
"Satire" is one of the dynamic types of art whose application to reform the disorders of human societies is considerable. Since the philosophy of revelation is guidance and reform, Qur'an, this unique divine art from which the art of rhetoric nourishes , at times utilizes this effective way to warn those who are not awaked by serious words, may it be that satire  awakes them. This article tries to present an accurate and comprehensive definition for satire and introduces its   qualified features from the Quranic point of view, while stating the exegetes position on  the characteristics of satire in the Holly Qur'an and  identifying its application in different  Quranic verses Eventually, with accurate reference to Quranic interpretations, this article tries to analyze the common manifestation of satire in various Quranic processes. These manifestations can be categorized in four frameworks as follows: Satirizing by means of obligation, allegory, simile to animals, and widening irony . This article, finally concludes that the ultimate goal of the Quranic satire is to modify the individual and the society and their learning from the theme which is employed in the satire.